IMPLEMENTASI ASESMEN DIAGNOSTIK NON-KOGNITIF DALAM UPAYA MENINGKATKAN AKTIVITAS BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X DI SMA NEGERI 1 FANAYAMA - Halawa, Nasrani (Universitas Nias Raya, 2025)
Learning assessment is an integrated part of learning activities in the classroom with the aim of feedback for teachers, learners, and parents to determine strategies for the next lesson. This study aims to determine the increase in learning activities of students by implementing non-cognitive diagnostic assessment in Class X economic subjects in SMA Negeri 1 Fanayama. The findings of the study showed that the results of non-cognitive diagnostic assessment tests showed the existence of 3 learning styles of Class X Aristotle students. After the application of learning adapted to the type of student learning, there are changes in student learning activities that show an increase when compared with learning activities before the known type of student learning. It can be concluded that the implementation of non-cognitive diagnostic assessment can improve the learning activities of students in Class X Aristotle on economic subjects. Suggestions offered by researchers, should be before organizing learning activities, teachers first conduct diagnostic assessments at the beginning of learning to make it easier for teachers to design learning that improves learning activities of students.